Thermal decomposition of trifluoromethoxycarbonyl peroxy nitrate, CF 3 OC(O)O 2 NO 2 - Manetti, Martin Diego (2008)
The thermal decomposition of trifluoromethoxycarbonyl peroxy nitrate, CF3OC(O)O2NO2, has been studied between 278 and 306 K at 270 mbar total pressure using He as a diluent gas. The pressure dependence of the reaction was also studied at 292 K between 1.2 and 270 mbar total pressure. The rate constant reaches its high-pressure limit at 70 mbar. The first step of the decomposition leads to CF3OC(O)O2 and NO2 formation, that is, CF3OC(O)O2NO2 + M ⇆ CF3OC(O)O2 + NO2 + M (k1, k−1). Reaction (−1) was prevented by adding an excess of NO that reacts with the peroxy radical intermediate and leads to carbonyl fluoride (CF2O), carbon dioxide (CO2), nitrogen dioxide (NO2), and small quantities of CF3OC(O)O2C(O)OCF3. The kinetics of reaction (1) was determined by following the loss of CF3OC(O)O2NO2 via IR spectroscopy. The temperature dependence of the decomposition follows the equation k1(T) = 1.0 × 1016 e−((111±3)/(RT)) for the exponential term expressed in kJ mol−1. The values obtained for the kinetic parameters such as k1 at 298 K, the activation energy (Ea), and the preexponential factor (A) are compared with literature data for other acyl peroxy nitrates. The atmospheric thermal stability of CF3OC(O)O2NO2 and its dependence with altitude is discussed.